Multiple magma sources and incremental assembly of the late Mesozoic Yunmengshan batholith, North China Craton: Constraints from zircon Hf-O isotopes and apatite geochemistry - Zi-Mu Li; Miao-Miao Ling-Hu; Shi Chen; Jin-Feng Sun; Ji-Heng Zhang; Ya-Dong Wu; Bao-Quan Zhou; Quan-Lin Hou; Jin-Hui Yang (Lithos, 2026)

Enhancing herbaceous biomass combustion in an industrial-scale CFB boiler using iron-based oxygen carriers as bed material - Guang Sun; Lin Li; Chong Liu; Tianxin Li; Heng Liu; Lunbo Duan (Fuel, 2026)

Flexible superhydrophilic amidoxime-based porous organic polymers linked by amide bonds for highly selective uranium extraction from seawater - Tianrui Li; Heng Zhao; Xiaoying Yuan; Chengjin Xu; Miaomiao Zhang; Chunfeng Li; Xiujing Peng; Xiaolei Liu; Guoxin Sun; Yu Cui (Journal of Environmental Chemical Engineering, 2026)

Combined berberine and glycyrrhetinic acid treatment confers antiviral and host-protective effects against CAPRV2023 infection in golden pompano (Trachinotus anak) - Weicong Li; Heng Sun; Haoyu Wang; Zhiyuan Huang; Deqi Wu; Haiqing Li; Liqun Wang; Yucong Huang (Fish & Shellfish Immunology, 2026)

Numerical modeling and experimental validation of uniform heating in a slot waveguide microwave system for continuous-flow high-viscosity liquids - Bowen Yan; Yuying Sun; Zhen Li; Haifeng Diao; Jianlian Huang; Heng Jiang; Xiaowei Yan; Nana Zhang; Huayu Yang; Huacheng Zhu; Wei Chen; Daming Fan (Chemical Engineering Journal, 2026)

EID1 blockade potentiates immunosurveillance against cancer metastasis via FPR1-mediated DC-NK crosstalk - Ziqi Jin; Xiao Zhang; Huijuan Zhang; Siying Qin; Siqi Zhang; Shuqing Zhang; Lin Xia; Peipei Li; Wen Xu; Peng Liu; Liwei Zhao; Ruidong Xue; et al. (Science China Life Sciences, 2026)

Biallelic hexose-6-phosphate dehydrogenase variants cause mitochondrial dysfunction underlying Parkinson’s disease - Miao Zhao; Yuwen Zhao; Juan Huang; Yu Guo; Wenjun Yu; Haiyan Hou; Yilin Huang; Xinying Du; Yu Zhang; Mujun Xie; Zuowen Ren; Haoyu Guan; et al. (Science Bulletin, 2026)

Evaluation of the immunological efficacy of EsxA subunit vaccine and DNA vaccine against Streptococcus iniae in golden pompano (Trachinotus anak) - Zhiyuan Huang; Heng Sun; Haoyu Wang; Xinlei Jia; Han Li; Dogbey Rejoice Abla; Weicong Li; Liqun Wang; Yishan Lu; Yucong Huang (Fish & Shellfish Immunology, 2026)

The Cangshan Mountain Precipitation Experiment (CAMPEX): Modulation of Precipitation by Typical Steep Mesoscale Terrain over Southwest China - Jian Li; Yin Zhao; Gaili Wang; Anlun Xu; Mengke Zhang; Tao Zhang; Baoju Dong; Guotao Zhang; Jian Huang; Yu Li; Cheng Yang; Bin Shu; et al. (Journal of Meteorological Research, 2026)

Stage-specific transcriptomic analysis reveals progressive immune activation, imbalance and escape during rhabdovirus infection in golden pompano (Trachinotus anak) - Yucong Huang; Heng Sun; Haoyu Wang; Wenjie Zheng; Xiaojuan Li; Deqi Wu; Weicong Li; Haiqing Li; Jia Cai; Liqun Wang (Aquaculture, 2026)

The regulatory role of HIRRV nucleoprotein on STING-mediated interferon response - Pingyuan Sun; Wenshuo Li; Xiaoqian Tang; Jing Xing; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Aquaculture, 2026)

A dual-functional single-crystalline layer boosts operational stability of organic light-emitting diodes - Gao-Da Ye; Guan-Ran Wang; Xue-Peng Wang; Su-Heng Li; Nai-Qi Wang; Hu Zhang; Yu-Ting Huang; Lingjie Sun; Yajing Sun; Fangxu Yang; Jin-Bei Wei; Yue-Feng Liu; et al. (Science Bulletin, 2026)

Water and salt transport behavior and deformation mechanism of carbonate saline soil under freeze-thaw cycles - Linjing Li; Yufeng Sun; Heng Chen; Dejian Li; Zichao Song; Xiaolin Weng (Cold Regions Science and Technology, 2026)

Mixture of Experts neural network for calculation of gamma-ray buildup factors - Zihui Yang; Yihang Sun; Heng Zhang; Chong Chen; Ziwen Mo; Zhixing Gu; Taosheng Li; Jie Yu (Annals of Nuclear Energy, 2026)

Building Drag Parameterization Including Anisotropy and Its Coupling with the Weather Research and Forecasting Model - Yuhang Tian; Zhenghui Xie; Jinbo Xie; Binghao Jia; Shuai Sun; Peihua Qin; Ruichao Li; Longhuan Wang; Heng Yan; Yanbin You (Advances in Atmospheric Sciences, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Soil-associated microorganisms: A natural source of biologically active compounds - Nigora Rustamova; Jakhongir Movlanov; Dildora Alimova; Heng Yin; Guozheng Huang; Maksud Isokov; Tang Li; Nasiba Khodjaeva; Aktam Nurniyozov; Sobirdjan Sasmakov; Batyr Khasanov; Dilmurod Murodullayev; et al. (Phytochemistry, 2026)

Palaeopolyploidy promoted ancient adaptation of Tibetan sclerophyllous oaks to aridity and cold triggered by mountain uplift - Jin-Jin Hu; Wen-Guang Sun; Jia Liu; Robert A. Spicer; Zhuo Zhou; Yong-Jiang Huang; Zhi-Min Li; Tao Su; Ting-Shen Han; He Tang; Lin-Bo Jia; Yun-Heng Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Abnormal lipoylation of aceF in proteobacteria induced by AgNPs during the storage of ozone-treated wastewater - Muxinjian Luo; Yuhe Wang; Qiang Sun; Heng Zhang; Jun Yuan; Weiyi Zhou; Xiyun Dong; Shihao Peng; Wenbo Cao; Hong Li; Huaili Zheng (Journal of Environmental Chemical Engineering, 2026)

Degradable Janus structured micro-nano fibrous membranes for effective particle filtration and antibacterial activity in high humidity working conditions - Gang Zhou; Zhuo Xu; Gang Li; Longjun Wang; Heng Sun; Mingyu Zhang; Yueying Xin; Yongmei Wang (Chemical Engineering Journal, 2026)

Phytostabilization potential of Amorpha fruticosa for cadmium and copper in mining soils: tolerance mechanisms and migration control - Xin Zheng; Ling Lei; Huayan Huang; Yuyuan Ouyang; Li Long; Maohang Jia; Shuang Feng; Zaijin Sun; Heng Xu (Plant and Soil, 2026)

EGR1 regulates degranulation and mediator release in C48/80-induced pseudo-allergic reactions - YiZhao Sun; Heng Li; Juntao Li; YaoJun Wang; Tongyun Long; Zhe Cui; Yanfen Zhang; Zhongcheng Liu (Immunologic Research, 2026)

A self-sustained and self-sensing ocean observation buoy: System integration and in-situ sea trial - Yunfei Li; Tianyi Tang; Heng Zhao; Lining Sun; Fusheng Zha; Huicong Liu (Ocean Engineering, 2026)

Targeting TNF-SDH axis in macrophages reverses abnormal succinate metabolism and M1 polarization to alleviate UVB-induced skin damage - Min Li; Yiming Guo; Xue Sun; Sihan Chen; Ran Zhang; Yujie Chen; Heng Gu; Xu Chen; Ni Lian (Journal of Photochemistry and Photobiology B: Biology, 2026)

Feather-based keratin hydrogels enhanced by multiple hydrogen bonding systems: Application in blasting dust suppression - Gang Zhou; Shu Li; Gang Li; Heng Sun; Yizhen Zhang; Xiaoqiang Cao; Bo Wei; Yan Zhang; Shuailong Li (Chemical Engineering Journal, 2026)

Sources, sinks, and isotopic fractionation of antimony in a karst catchment: constraints on multi-media migration and biogeochemical cycling - Yu Lin; Guangyi Sun; Xinyu Li; Yunjie Wu; Yu Cheng; Heng Yao; Xinbin Feng (Geochimica et Cosmochimica Acta, 2026)

Flavor enhancement of corn oil through the solid-state complex-enzyme hydrolysis: Process optimization and mechanistic insights - Guohao Sun; Shangde Sun; Yulan Liu; Hao Zhang; Yuxiang Ma; Yaoyao Zhang; Heng Du; Talha Ashfaq; Xuze Zhang; Zisong Li; Aiyue Wang (Food Chemistry, 2026)

The Spatiotemporal Evolution of Sugarcane Growth Based on Remote Sensing Monitoring and its Influence Factors Detection Regression Analysis in Guangxi, China - Yun-chuan Yang; Chang-zheng Wei; Xin-chang Xie; Li-ping Liao; Li-qing Liang; Zong-heng Li; Meng-dong He; Chong-xun Mo; Xun-gui Li; Gui-kai Sun (Sugar Tech, 2026)

Endometrial microbiota-dimethylglycine-Treg cell axis affects endometrial receptivity in recurrent implantation failure - Fen-Ting Liu; Ping Zhou; Feng Deng; Bao-Ying Liao; Zi Yang; Di Sun; Heng Pan; Yang Yu; Shuo Yang; Rong Li (Science China Life Sciences, 2026)

Expression of PSTPIP1 in Renal Cell Carcinoma and Its Prognostic Value - Yiyang Chen; Xiaowen Qin; Li Sun; Pu Zhang; Zhenghong Liu; Bin Zheng; Yixuan Mou; Haichang Li; Heng Wang; Dahong Zhang (Biochemical Genetics, 2026)

In vitro screening and in vivo evaluation of anti-virulence herbal compounds against Streptococcus agalactiae in tilapia (Oreochromis niloticus) - Ming-Li Xiang; Zi-Chen Zhao; Gui-Hua Li; Wei Tang; En-Peng Chen; Shui-Feng Qin; Yan Wang; Heng-Wei Deng; Zhi-Hong Zhong; Yun Sun; Wei-Liang Guo; Yong-Can Zhou (Aquaculture, 2026)

Angelicin attenuates sepsis-associated splenic injury by targeting NF-κB/JAK2/STAT3 and PI3K/Akt pathways to inhibit inflammation and apoptosis - Enzhuang Pan; Huilin Sun; Zhihao Ma; Shasha Zhang; Yedan Liu; Zihan Xu; Yusa Li; Xiaomin Jin; Heng Wang; Jingquan Dong (Toxicology and Applied Pharmacology, 2026)

Simulation study on methane-synergized recycled flue gas modified reburning and optimization of combustible components in syngas - Wenda Zhang; Yukai Li; Chenxi Bai; Doudou Miao; Yijun Zhao; Shaozeng Sun; Heng Liang (Fuel, 2026)

Chiral CD@Ag2O nanoparticle-mediated highly efficient antibacterial activity based on synergistic multi-pathway interactions - Xiang Li; Qi Ding; Si Li; Junru Li; Heng Zhang; Shan Sun; Hengwei Lin; Peng Wang (Chemical Engineering Journal, 2026)

Revealing the Key Role of Chelates in Enhancing Fertilizer Performance: A Review - Kejian Fu; Yucui Sun; Yingying Li; Darun Yang; Heng Li (Journal of Soil Science and Plant Nutrition, 2026)

Electrochemical nitrate reduction for sustainable nitrogen and resource cycles: Progress and prospects - Zhenzhou Li; Jiawei Liang; Yifan Dai; Shihao Fu; Jialong Chen; Yunyang Sun; Jinlong Wang; Han Zhang; Daliang Xu; Jiaxuan Yang; Heng Liang (Critical Reviews in Environmental Science and Technology, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Experimental Investigation of Macro- and Microscopic Degradation and Damage Mechanisms in Granite Subjected to Microwave Radiation under True Triaxial Compression - Sheng-Qi Yang; Bo-Wen Sun; Heng Li (Rock Mechanics and Rock Engineering, 2026)

Copper exposure induces autophagy and angiogenesis in liver cell via ATF4 activation independent of TFEB - Meng Zhang; Yi-Ge Zhang; Yu-Tian Shi; Xiao-Chuan Qu; Yu-Heng Li; Ji-Xing Miao; Guo-Ming Sun; Peng Ge; Bao-Qin Liu (Toxicology, 2026)

Cadmium accumulation and isotope fractionation in soil–oilseed rape (Brassica napus L.) system in a typical Karst region - Weihai Yu; Guangyi Sun; Heng Yao; Xian Wu; Zhe Liu; Yu Lin; Yu Cheng; Jiang Li; Hua Zhang; Xinbin Feng (Journal of Hazardous Materials, 2026)

Mapping the Cross-species Brain Connectivity Atlas and Hemispheric Asymmetry of the Temporal Pole in Humans and Macaques - Qinyao Sun; Shunli Zhu; Futing Yang; Zhigang Chen; Heling Li; Heng Shao; Hong Wang; Sangma Xie; Jiaojian Wang (Neuroscience Bulletin, 2026)

A novel deep learning system for STEMI prognostic prediction from multi-sequence cardiac magnetic resonance - Yifan Chen; Meng Jiang; Chao Xia; Hang Zhao; Panpan Ke; Sheng Chen; Heng Ge; Keran Li; Xu Wang; Yufei Wang; Yezi Chai; Qiming Liu; et al. (Science Bulletin, 2025)

Metal–phenolic networks improve biocontrol effect of Bacillus velezensis DM14 against pear anthracnose - Jianfeng Du; Heng Li; Shenjie Liu; Jiawei Tang; Xin Zhao; Yiming Liu; Limin Wu; Yue Li; Qixiong Gao; Fuxin Sun; Ninghai Lu; Xueliang Tian; et al. (Pesticide Biochemistry and Physiology, 2025)

Tailoring the asymmetric structure of Cu-Co bimetallic catalysts to promote peroxydisulfate activation for pollutant degradation - Li-Ming Sun; Qin-Chen Li; Yong-Sheng Tan; Qi-Nian Wang; Yi-Lin Lu; Yi-Jun Zhang; Dong-Hua Xie; Heng-Heng Guo; Xing Zhang (Journal of Environmental Chemical Engineering, 2025)

Low-molecular-weight dextran sulfate sodium as novel heparanase inhibitor preventing breast cancer metastasis in mice by inhibiting migration and angiogenesis - Yidian Mo; Guohao Song; Linbo Fu; Yuchao Wang; Tongtong Geng; Ao Sun; Baodi Gou; Xiangbao Meng; Liangren Zhang; Heng Wang; Zhongjun Li; Zhongtang Li (Carbohydrate Polymers, 2025)

Pivotal epitopes for islet antigen-specific CD8+ T cell detection improve classification of suspected type 1 diabetes with the HLA-A*0201 allele - Yang Chen; Min Shen; Yong Gu; Xinyu Xu; Lingling Bian; Fan Yang; Shuang Chen; Li Ji; Jin Liu; Jing Zhu; Zheng Zhang; Qi Fu; et al. (Immunologic Research, 2025)

Numerical investigation on the applicability of turbulent-Prandtl-number models under the influence of thermal boundary conditions for liquid lead–bismuth eutectic - Zhelun Ai; Yumeng Sun; Heng Miao; Yi Yang; Jie Li; Wenbin Wu (Annals of Nuclear Energy, 2025)

Optimal Ship Pipe Route Design: A MOA*-Based Software Approach - Zongran Dong; Kai Li; Heng Chen; Chenghao Sun (Journal of Marine Science and Engineering, 2025)
For the ship pipe routing design (SPRD) problem, previous studies have mainly employed bio-inspired algorithms such as multi-objective ant colony optimization (MOACO), non-dominated sorting genetic algorithm II (NSGA-II), and multi-objective particle swarm optimization (MOPSO). This paper proposes a novel approach based on the multi-objective A* (MOA*) algorithm to solve the SPRD. First, the optimization objectives and constraints of the SPRD problem are defined, and then an MOA*-based routing framework is developed. The time and space complexities of the approach are analyzed, and key components such as the cost functions, the solution dominance relationship, dynamic probability-based pruning, and neighbor node exploration strategy are designed to enhance solution diversity and search efficiency. Additionally, a space cascade expansion method is proposed to improve the computational efficiency of the MOA* in large-scale grid spaces. Comparative studies with MOACO, NSGA-II, GA-A*, and gray wolf optimization (GWO) on simulated cases of varying complexities and practical piping scenarios demonstrate the effectiveness of the MOA*. Furthermore, the applicability of the MOA* is validated against practical piping requirements, including the rapid generation of sub-optimal solutions, non-orthogonal routing, and partitioned pipe layouts. Experimental results, supported by a C++/OpenGL-based prototype software, show that the MOA* requires no extensive parameter tuning, exhibits stable computational efficiency and optimization capability, and demonstrates competitive performance in Pareto-optimal diversity compared with other algorithms.

Corrigendum to “Immunological characteristics of the recombinant pseudorabies virus with chimeric PCV Cap protein in pigs” [Vet. Microbiol. 305 (2025) 110529] - Chenhe Lu; Wenjing Chen; Heng Chen; Gang Xing; Jiayu Ma; Hui Zhou; Linglong Qin; Da Liu; Shiping Sun; Peng Peng; Haimin Li; Yulan Jin; et al. (Veterinary Microbiology, 2025)

Multi-scale analysis of contaminant transport in the ice-covered channel flows with bed absorption - Feifei Wang; Heng Li; Huaxiang Li; Bin Sun; Sifan Zhao; Zhiwei Li (Journal of Hydrology, 2025)

A multiscale peridynamic simulation on thermal-mechanical coupling behavior and damage failure mechanism of granite - Heng Li; Sheng-Qi Yang; Rui Yong; Shi-Gui Du; Bo-Wen Sun; Su-Sheng Wang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Rapid and non-destructive detection of formaldehyde adulteration in shrimp based on deep learning-assisted portable Raman spectroscopy - Chencheng Wei; Jiheng Zhang; Gaozheng Li; Yi Zhong; Zhaoting Ye; Handong Wang; Kezhi Li; Yuanzi Wu; Yuezhong Wu; Heng Luo; Qi Sun; Zuquan Weng (Food Chemistry, 2025)

Topography-engineered cobalt-based microparticles for biofilm-eradicating medical device disinfection: Overcoming antibacterial resistance through mechano-bactericidal action - Ke Cheng; Shan Sun; Wenhao Zheng; Heng Zhang; Henggang Wang; Shang Gao; Si Li; Hengwei Lin; Peng Wang (Chemical Engineering Journal, 2025)

Water oxidation catalysts from electrochemical intercalating [PW12O40]3‐ and synthesizing layered double hydroxide on high conductivity rGO@Ni foam - Xiaoyan Zhu; Zhipeng Sun; Minghe Du; Yi Liu; Huixi Li; Heng Deng; Chunjie Yan; Shengping Wang (Applied Clay Science, 2025)

Soil nitrogen availability increases the abundance of nitrogen-fixing plants in subtropical forests - Xibin Sun; Scott X. Chang; Matthew D. Petrie; Yixue Hong; Meimei Li; Zilong Ma; Heng Huang; Zhenchuan Wang; Chengjin Chu; Fuchen Luan; Hao Chen (Soil Biology and Biochemistry, 2025)

Enhanced sludge dewatering by low-temperature heat treatment with polyacrylamide under near-neutral conditions: Focusing on microbial community and antibiotic resistance genes - Dongqin He; Tingting Zhu; Mingkai Sun; Bo Bao; Pan Heng; Hongwei Luo; Jun Li (Journal of Environmental Chemical Engineering, 2025)

Low-cost municipal solid waste incineration fly ash adsorbents for phosphate recovery: A potential green treatment process - Qianyi Liu; Jingjing Sun; Xuefeng Liu; Yan Li; Chengcheng Shen; Samir I. Gadow; Heng Li; Yanlong Zhang (Journal of Environmental Chemical Engineering, 2025)

Ultrasound triggered spatial-temporal NO gas release to enhance sonodynamic therapy and immune checkpoint blockade therapy against pancreatic cancer - Wanrui Shi; Jianfeng Zhang; Ruiqi Wu; Shiti Shama; Shi Tan; Heng Xue; Yan Sun; Qingshuang Tang; Suhui Sun; Rui Tang; Guotao Feng; Xiaoda Li; et al. (Chemical Engineering Journal, 2025)

Agricultural SDHIs Induce Azole Resistance in Aspergillus fumigatus via Mitochondrial Sdh1 Suppression - Heng Zhang; Zhangling Zhu; Mengqi Peng; Sijie Liu; Xiao Gong; Tian Chen; Qingwen Hu; Linyun Li; Zha-xi Dun-zhu; Lha-zom Drol-ga; Yi Sun (Mycopathologia, 2025)

PdSe2/WS2/PdSe2 unipolar barrier photodetector for visible-infrared polarization detection, synaptic plasticity simulation and neuromorphic visual system - Wenhao Fan; Hui Yan; Heng Li; Xinjian Liu; Yu Zhang; Weijie Bai; Mengyang Li; Yanxia Li; Jin Zhang; Jiayu Zhao; Shishuai Sun; Qingguo Wang; et al. (Chemical Engineering Journal, 2025)

Genetic mapping and isolation of Rht28, a locus on wheat chromosome arm 2AL affecting plant height, grain size, and grain weight - Zhuo Liu; Jiaojiao Zhu; Qiuyue Zhao; Yiwen Cao; Qiuhong Wu; Junru Zhang; Yongxing Chen; Qingpeng Sun; Runzhi Li; Heng Tang; Zhiyong Liu; Jun Han (Theoretical and Applied Genetics, 2025)

Identification of the sources and migration of antimony in karst terraces via Sb stable isotopes - Yunjie Wu; Guangyi Sun; Yu Lin; Xinyu Li; Yu Cheng; Heng Yao; Xinbin Feng (Journal of Hazardous Materials, 2025)

Protective effect of cartilage oligomeric matrix protein (COMP) on osteoarthritis-like chondrocytes based on the nuclear factor kappa B (NF-κB) pathway - Wei Weng; Rong Wu; Zhenguo Sun; Haidong Li; Yuxin Shen; Heng Li; Jikang Min (Journal of Molecular Histology, 2025)

Microbial behavior drives structure and composition changes during bio-cake evolution and implications for membrane fouling mitigation - Yazhou Sun; Zedong Lu; Chaoran Liu; Xing Li; Zhiwei Zhou; Jiawei Ren; Chen Li; Heng Liang (Chemical Engineering Journal, 2025)

Comparative analysis of modeling methods and prediction accuracy for Japanese sardine habitat under three climate scenarios with differing greenhouse emission pathways - Yuyan Sun; Delong Xiang; Jianhua Wang; Keji Jiang; Hanji Zhu; SiSi Huang; Famou Zhang; Yang Li; Heng Zhang (Marine Pollution Bulletin, 2025)

Immunological characteristics of the recombinant pseudorabies virus with chimeric PCV Cap protein in pigs - Chenhe Lu; Wenjing Chen; Heng Chen; Gang Xing; Jiayu Ma; Hui Zhou; Linglong Qin; Liu Da; Shiping Sun; Peng Peng; Haimin Li; Yulan Jin; et al. (Veterinary Microbiology, 2025)

Unveiling fungal degradation pathways for polyurethane and polyethylene through enrichment cultures and metabolic analysis - Eyalira Jacob Okal; Jie Zhou; Yanfei Wu; Tingfang Zhong; Yue Tang; Zhengyu Sun; Ruifang Xu; Yuwei Hu; Na Hu; Jingxian Li; Samantha C. Karunarathna; Peter E. Mortimer; et al. (International Biodeterioration & Biodegradation, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Anti-ferroptosis effects of undescribed abietane diterpenoids from Prunella vulgaris subsp . hispida (Benth.) Hultén - Heng-Li Yan; Xiao-Qiao Yang; Han-Fei Liu; Fen-Cong Pan; Jin-Yu Li; Wei-Dong Pan; Ni Zhang; Hua-Yong Lou; Chao Sun (Natural Product Research, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

High surfacial positive charge density of quaternary ammonium salt-amidoxime bifunctional copolymers promotes the ultrafast extraction of uranium (VI) from seawater - Tianrui Li; Heng Zhao; Miaomiao Zhang; Xiujing Peng; Wenting Li; Guoxin Sun; Yu Cui (Journal of Water Process Engineering, 2025)

Thermal-fluid coupled fracture behavior of fissured granite in a 3D crystal model - Heng Li; Sheng-Qi Yang; Bo-Wen Sun; Zhen Yang; Zhi-Jin Dong; Pin-Qiang Mo (Engineering Geology, 2025)

Monitoring the circumferential cracking of inner concrete core in prestressed concrete cylinder pipe during wire-wrapping using distributed optical fiber sensors - Shuai Liu; Yanlong Li; Ye Zhang; Minghui Ma; Wen Qiu; Lei She; Heng Zhou; Kangping Li; Kaiyu Sun (Tunnelling and Underground Space Technology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Improving the redox kinetics and hydrogen yield of calcium-modified ilmenite in chemical looping process by potassium addition - Zhuang Sun; Weichen Zeng; Heng Li; Junichiro Otomo (Chemical Engineering Journal, 2025)

From metabolomics to therapeutics: identifying causal metabolites and potential drugs for the treatment of osteoarthritis - Heng Li; Jingyan Sun; Jiewen Zhang; Yang Chen; Yiwei Zhao; Ruomu Cao; Ning Kong; Xudong Duan; Huanshuai Guan; Run Tian; Kunzheng Wang; Pei Yang (Inflammopharmacology, 2025)

The research of nicotinamide and β-arbutin on reducing melanin content in the skin of leopard coral grouper (Plectropomus leopardus) - Zhi Bin Sun; Shi Ying Liu; Xin An Wang; Ai Jun Ma; Zhi Hui Huang; Zhi Feng Liu; Wei Heng Sun; Peng Fei Yan; Dong Hui Gou; Hui Yu Xiao; Hao Zhe Li; Vorathep Muthuwan; et al. (Aquaculture, 2025)

Mass mortality associated with carpione rhabdovirus in golden pompano (Trachinotus ovatus) in China: First report - Heng Sun; Jie Huang; Haoyu Wang; Yule Zhang; Qing Fei; Jie Zhou; Lindi Yang; Yanping Li; Jichang Jian; Yishan Lu; Shuanghu Cai; Yucong Huang (Aquaculture, 2025)

Enhancing performance in gravity-driven membrane systems through pre-coating with aluminum-based flocs: Mechanism and energy saving analysis - Yazhou Sun; Zedong Lu; Xing Li; Shaozhu Wang; Jianyong Feng; Yanling Yang; Zhiwei Zhou; Jiawei Ren; Heng Liang (Journal of Environmental Management, 2025)

Enhancing butyrate synthesis and intestinal epithelial energy supply through mixed probiotic intervention in dextran sulfate sodium-induced colitis - Heng Zhang; Jingzhou Sun; Aowen Xie; Huiqin Yang; Yingjun Li; Yuxia Mei; Jinshan Li; Lei Xiao; Yangyang Liu; Yunxiang Liang (Food Bioscience, 2025)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

CO2-responsive multifunctional label based on chitosan and hyaluronic acid for visualizing and maintaining postharvest freshness - Haiyu Du; Xinru Liu; Xiaoli Sun; Heng An; Yiyi Li; Zhu Zhu; Yongqiang Wen (Food Hydrocolloids, 2024)

Predicting plateau atmospheric ozone concentrations by a machine learning approach: A case study of a typical city on the southwestern plateau of China - Qiyao Wang; Huaying Liu; Yingjie Li; Wenjie Li; Donggou Sun; Heng Zhao; Cheng Tie; Jicang Gu; Qilin Zhao (Environmental Pollution, 2024)

Nature-inspired ultrathin wood-based interfacial solar steam generators for high-efficiency water purification - Min Li; Yating Sun; Yuzhang Lei; Gonggang Liu; Heng Jiang; Yong Wang; Shanshan Chang; Xianjun Li; Jinbo Hu (Desalination, 2024)

Dual activation of soybean resistance against Phytophthora sojae by pectin lyase and degraded pectin oligosaccharides - Guangzheng Sun; Yeqiang Xia; Kuikui Li; Qinsheng Zhu; Feifei Ding; Hui Gu; Zhichao Zhang; Xinrui Li; Xuan Mi; Jun Chen; Ruoting Yao; Sicong Zhang; et al. (Science China Life Sciences, 2024)

High-Precision Re-Os Geochronology of the newly Discovered Lihefu Deposit Reveals the ∼145 Ma Mo Mineralization in Daye District, Eastern China - Hao Hu; Longpeng Li; Heng Luo; Yi Huang; Fang Sun; Jinhua Liu; Xiaodong Deng (Journal of Earth Science, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

Response Mechanism of Dynamic Tensile Mechanics in Granite Under Microwave Irradiation: Insights from Experiments and Simulations - Bo-Wen Sun; Sheng-Qi Yang; Man Huang; Heng Li; Wen-Ling Tian; Yan-Hua Huang (Rock Mechanics and Rock Engineering, 2024)

Simulating the changes of the habitats suitability of chub mackerel (Scomber japonicus) in the high seas of the North Pacific Ocean using ensemble models under medium to long-term future climate scenarios - Yuyan Sun; Heng Zhang; Keji Jiang; Delong Xiang; Yongchuang Shi; Sisi Huang; Yang Li; Haibin Han (Marine Pollution Bulletin, 2024)

Water flush boosts performance of elemental sulfur-based denitrification packed-bed systems: Optimization and mechanisms - Jia-Min Xu; Heng Dong; Hao-Ran Xu; Yi-Lu Sun; Yang Yu; Li-Ying Zhang; Gen-Ping Yi; Wen-Ke He; Chang-Min Wu; Ai-Jie Wang; Hao-Yi Cheng (Bioresource Technology, 2024)

Molecular insights into the interactions of theaflavin and epicatechin with different lipid bilayer membranes by molecular dynamics simulation - Rong-zu Nie; Huo-min Luo; Jing-yu Chen; Li-heng Sun; Zi-bo Wang; Zhen-ping Zhang; Ya-ru Bao (Chemistry and Physics of Lipids, 2024)

Paleoenvironmental evolution and organic matter accumulation of the lower Cambrian Maidiping marine black shales in the intracratonic basin, western margin of Sichuan Basin, South China - Guodong Xia; Yuehao Ye; Shugen Liu; Heng Wang; Jinmin Song; Wei Sun; Bo Ran; Kun Jiao; Guoliang Xie; Bin Deng; Zhiwu Li; Yun Zeng (International Geology Review, 2024)

A wearable strain sensor with self-cleaning capability for underwater applications - Jing Liu; Junze Zhang; Weiwei Sun; Yushu Qian; Jingge Liu; Heng Zhai; Zeyu Zhao; Kaili Chen; Yi Li; Gang Li (Chemical Engineering Journal, 2024)

Heterobimetallic praseodymium-nickel active sites with Pr-N4C2 and Ni-N4 moieties enabling synergistic catalysis of CO2 electroreduction - Heng Zhang; Yajie Cao; Min Sun; Yang Liu; Yan Wang; Haorun Li; Riguang Zhang; Xiaojun Gu; Shanghong Zeng (Chemical Engineering Journal, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Environmental Influences on Illex argentinus Trawling Grounds in the Southwest Atlantic High Seas - Delong Xiang; Yang Li; Keji Jiang; Haibin Han; Yuhan Wang; Shenglong Yang; Heng Zhang; Yuyan Sun (Fishes, 2024)
To understand the spatial temporal distribution characteristics of Illex argentinus caught by trawl fishing vessels in the Southwestern Atlantic Ocean and their relationship with key marine environmental factors, this study analyzed the temporal and spatial changes in the fishing ground center of trawl vessels at the ten-day scale from December 2019 to May 2022, combining Chinese trawl fishing log data marine environmental data with satellite remote sensing marine environmental data. Utilizing the Maxent model, ten-day intervals were used as the temporal scale, and ten marine environmental factors, including sea surface temperature, sea surface height, sea surface salinity, chlorophyll concentration, temperature at 50 m and 100 m depth, and the meridional and zonal velocities of ocean currents were quantitatively analyzed to explore the correlation between the spatial distribution of catch and environmental factors. The study reveals that the trawl fishing grounds for Illex argentinus are divided into southern and northern grounds. The southern grounds first appear near 45°20′ S in December, gradually moving southeastward in February and March. The northern grounds do not appear until April, near 42° S in the high seas. On the ten-day time scale, the central fishing grounds of Illex argentinus show significant spatial variability but minor interannual differences. The Maxent model results indicate that sea surface temperature and chlorophyll a concentration are the key environmental factors influencing the spatial and temporal variability of the high seas trawl fishing grounds for most of the time, with high environmental contribution rates during the fishing season. While the range of suitable habitats with an HSI > 0.6 identified by the Maxent model varies significantly between years, a pattern is observed where the range expands at the start and end of the fishing season and contracts during the peak fishing season. This suggests that a more concentrated range of suitable habitats is conducive to accurate predictions of trawl fishing grounds, enabling efficient fishing operations.

Mechanically treated Mn2O3 triggers peracetic acid activation for superior non-radical oxidation of micropollutants: Identification of reactive complexes - Yudan Dong; Chuan-Shu He; Si Sun; Jiali Liu; Zhi-Hui Xie; Jie-Yuan Li; Peng Zhou; Heng Zhang; Fan Dong; Bo Lai (Water Research, 2024)

Multiple stimulus responsive of a novel naphthalenediimide-based 2D alkaline-earth metal MOF material: Hydrochromism, amine-/acid-induced chromism and ionochromism as well as visual artificial film application - Rong Huo; Ting Zhang; Li Xian Sun; Li Na Zhao; Yong Heng Xing; Feng Ying Bai (Chemical Engineering Journal, 2024)

A new monsoon circulation index defining precipitation variability in the East Asian summer monsoon northern marginal zone - Congxi Fang; Yu Liu; Huiming Song; Qiufang Cai; Heng Liu; Qiang Li; Changfeng Sun (Theoretical and Applied Climatology, 2024)

Morphological and physiological plasticity of Catalpa bungei roots under partial root-zone drought as affected by nitrogen forms - Tiantian Sun; Ruohan Ren; Mingming Xing; Qiuxiao Duan; Lang Zhao; Wenwen Yan; Yang Fang; Senyan Zhang; Hao Dong; Mengran Wang; Qimeng Heng; Wenyi Chen; et al. (New Forests, 2024)

Microfluidic device featuring micro-constrained channels for multi-parametric assessment of cellular biomechanics and high-precision mechanical phenotyping of gastric cells - Yang Heng; Xinyu Zheng; Youyuan Xu; Jiaqi Yan; Ying Li; Lining Sun; Hao Yang (Analytica Chimica Acta, 2024)

Nitrogen addition does not alter symmetric responses of soil respiration to changing precipitation in a semi-arid grassland - Lingjie Kong; Jian Song; Jingyi Ru; Jiayin Feng; Jiawei Hou; Xueke Wang; Qingshan Zhang; Haidao Wang; Xiaojing Yue; Zhenxing Zhou; Dasheng Sun; Jiajia Zhang; et al. (Science of The Total Environment, 2024)

Sulfur and nitrogen co-metabolism during composting: A role of sodium sulfide in regulating microbial communities and functional genes - Shuaipeng Liu; Heng Lu; Ao Wang; Xiaojing Chen; Hongmei Yang; Xueling Liang; Ru Sun; Xiaoli Wen; Qunliang Li (Journal of Environmental Chemical Engineering, 2024)

Enhanced removal of Pb2+ and Congo red from aqueous solutions using hierarchically porous melamine sponge/polyvinyl alcohol/Zr-MOF composites - Heng Zhao; Tianrui Li; Miaomiao Zhang; Xiujing Peng; Chengjin Xu; Jianhui Su; Zhen Yang; Xiaolei Liu; Guoxin Sun; Yu Cui (Journal of Environmental Chemical Engineering, 2024)

Permanganate-assisted pilot-scale gravity-driven membrane (GDM) filtration in treating Mn(II)-containing groundwater: Fast startup and mechanism - Zheng Ke; Heng Liang; Yitong Sun; Tianli Wang; Jiaoying Luo; Yuchao Tang; Guibai Li; Xiaobin Tang; Jinlong Wang (Journal of Environmental Chemical Engineering, 2024)

Synergistically accelerating capture and catalytic conversion of polysulfides by Co@NCNT-MoSe2 nanocomposite modified separator for advanced Lithium-Sulfur batteries - Xinwei Wang; Kangning Xu; Jiayi Guo; Zeyang Li; Siyang Liu; Lianshan Sun; Jianxun Zhao; Heng Liu; Wanqiang Liu; Fang Wang (Chemical Engineering Journal, 2024)

Adsorption characteristics of Ag+ on sphalerite surface: a combined experimental and first-principle study - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Environmental Science and Pollution Research, 2024)

Pathogenicity and horizontal transmission evaluation of a novel isolated African swine fever virus strain with a three-large-fragment-gene deletion - Han Gao; Dongdong Di; Qianwen Wu; Jie Li; Xing Liu; Zhiying Xu; Sijia Xu; Chengyu Wu; Lang Gong; Yankuo Sun; Guihong Zhang; Hongjun Chen; et al. (Veterinary Microbiology, 2024)

Relationships among the climate-relevant gases during the Southern Ocean bloom season - Zhang Miming; Heng Sun; Jiexia Zhang; Yanfang Wu; Zhongyong Gao; Liyang Zhan; Jinpei Yan; Jing Li (Science of The Total Environment, 2024)

First insights into the bioaccumulation, biotransformation and trophic transfer of typical tetrabromobisphenol A (TBBPA) analogues along a simulated aquatic food chain - Chuan-Sheng Sun; Sheng-Wu Yuan; Rui Hou; Si-Qi Zhang; Qian-Yi Huang; Lang Lin; Heng-Xiang Li; Shan Liu; Yuan-Yue Cheng; Zhi-Hua Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Experimental and computational study on the adsorption mechanism of silver ions on galena surface - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Journal of Water Process Engineering, 2024)

Application of skeleton builders to sludge dewatering and disposal: A critical review - Purui Bao; Chunyan Du; Yifu Li; Heng Jiang; Lu Zhou; Guanlong Yu; Shiquan Sun; Lean Zhou; Xue Li; Junyi Teng; Xiaowen Wang; Junchao Wang (Science of The Total Environment, 2024)

Atomic ruthenium doping in collaboration with oxygen vacancy engineering boosts the hydrogen evolution reaction by optimizing H absorption - Dong Sui; Ruishen Luo; Shumin Xie; Heng Zhang; Tiantian Ma; Hao Sun; Tong-Tong Jia; Jing Sun; Xingyun Li (Chemical Engineering Journal, 2024)

Cost-effective identification of the field maturity of tobacco leaves based on deep semi-supervised active learning and smartphone photograph - Tong Sun; Chaoqun Xue; Yang Chen; Luyao Zhao; Chenchen Qiao; Aoyu Huang; Feitao Li; Chao Liu; Heng Wang; Yongfeng Yang; Qian Yao; Gaojie Wang; et al. (Computers and Electronics in Agriculture, 2023)

Dual-functional smart indicator for direct monitoring fruit freshness - Wenmin Zhang; Heng An; Xiaoli Sun; Haiyu Du; Yiyi Li; Mengyao Yang; Zhu Zhu; Yongqiang Wen (Food Packaging and Shelf Life, 2023)

Classification of Glomerular Pathology Images in Children Using Convolutional Neural Networks with Improved SE-ResNet Module - Xiang-Yong Kong; Xin-Shen Zhao; Xiao-Han Sun; Ping Wang; Ying Wu; Rui-Yang Peng; Qi-Yuan Zhang; Yu-Ze Wang; Rong Li; Yi-Heng Yang; Ying-Rui Lv (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Photocatalytic membrane coated with α-Fe2O3/Fe3O4 for enhanced filtration performance and antifouling property in surface water treatment - Yuanqing Guo; Quan Liu; Xiaobin Tang; Heng Liang; Guibai Li; Liwei Yang; Lu Wang; Xiaoling Li; Yan Sun (Chemosphere, 2023)

A stable spherical MOF-derived Mnx-Fe2O3/C catalysts for low-temperature CO-SCR - Cheng Li; Yong Shi; Qi Dong Zhao; Wei Xiong; Yue Ding; Jian Heng Sun; Ying Lei Huang; Zhong Fei Zhao (Chemical Engineering Journal, 2023)

Crystal accumulation induced Sr/Y variation: Insights from a rear-arc pluton in the western Central Qilian Belt, NW China - Xue Li; Chao Wang; Mei-yun Wu; Ji-heng Zhang; Xiao-hui Zhu; Joseph G. Meert; Xiao-kui Sun; Hang Li; Jiang-bo Hao; Zun-pu Yu (Journal of Asian Earth Sciences, 2023)

A tradeoff between denitrification and nitrate leaching into the subsoil in nitrate-rich vegetable soils treated by reductive soil disinfestation - Hui-Min Zhang; Yu Liu; Ying-Hua Zhang; Yong Li; Zhao-Xiong Chen; Xin Sun; Hang Jing; Jing Wang; Ahmed S. Elrys; Mao-Heng Zhang; Zu-Cong Cai; Yi Cheng (Agriculture, Ecosystems & Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Selective elimination of sulfonamide antibiotics upon periodate/catechol process: Dominance of quinone intermediates - Shuai Yang; Yang Shi; Xinhao Wang; Yang Liu; Yi Ren; Wei Li; Heng Zhang; Xiaoqiang Dai; Weiyi Sun; Bo Lai (Water Research, 2023)

In-situ formation of magnetic sodium ferric silicate/ferric oxide S-scheme heterojunction with efficiently removing tetracycline in photo-Fenton-like reaction - Heng He; Yongli Li; Chen Lai; Junshu Wu; Lingmin Sun; Meng Xu; Jinshu Wang (Journal of Cleaner Production, 2023)

Design and operation insights concerning a pilot-scale S0-driven autotrophic denitrification packed-bed process - Yi-Lu Sun; Zhuo-Ran Li; Xue-Ning Zhang; Heng Dong; Zhi-Min Qian; Shan Yi; Wei-Qin Zhuang; Hao-Yi Cheng; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Growth of spiral ganglion neurons induced by graphene oxide/oxidized bacterial cellulose composite hydrogel - Lin Shi; Guodong Hong; Chuntao Chen; Xueqian Li; Heng Zhang; Renjie Chai; Dongping Sun (Carbohydrate Polymers, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Quantitative proteomics provides an insight into germination‐related proteins in the plant pathogenic fungi Phomopsis vexans - Zhou Heng; Qian You; Baojuan Sun; Zhiliang Li; Xiaoqing Sun; Junlin Huang; Ying Li; Hengming Wang; Xiaowan Xu; Zhenxing Li; Chao Gong; Tao Li (European Journal of Plant Pathology, 2023)

Life cycle assessment of bio-fermentation ethanol production and its influence in China's steeling industry - Lingyun Zhang; Qun Shen; Cheng Heng Pang; Wei Chao; Shuhuan Tong; Kien Woh Kow; Edward Lester; Tao Wu; Li Shang; Xuehang Song; Nannan Sun; Wei Wei (Journal of Cleaner Production, 2023)

Molecular regulation of immunity in tea plants - Lu Rui; Jia-yi Su; Tao Li; Jia-miao Sun; Guang-heng Wu (Molecular Biology Reports, 2023)

Protective effect of bone morphogenetic protein-7 induced differentiation of bone marrow mesenchymal stem cells in rat with acute spinal cord injury - Xudong Sun; Maoyong Li; Shiyuan Huang; Heng Zhang; Kuanxin Li (Functional & Integrative Genomics, 2023)

Distribution patterns of landslides triggered by the 2022 Ms 6.8 Luding earthquake, Sichuan, China - Jian-qiang Zhang; Zong-ji Yang; Qing-kai Meng; Jiao Wang; Kai-heng Hu; Yong-gang Ge; Feng-huan Su; Bo Zhao; Bo Zhang; Ning Jiang; Yu Huang; Zai-yang Ming; et al. (Journal of Mountain Science, 2023)

Release and migration of Hg during desulfurization wastewater evaporation process: Whole process evaluation by experimental and theoretical study - Heng Chen; Lingxiao Zhan; Hao Zhou; Zhihao Li; Jiawei Chen; Zongkang Sun; Hao Wu; Linjun Yang (Journal of Hazardous Materials, 2023)

Correction: RNA m6A methylation promotes the formation of vasculogenic mimicry in hepatocellular carcinoma via Hippo pathway - Kailiang Qiao; Yantao Liu; Zheng Xu; Haohao Zhang; Heng Zhang; Chao Zhang; Zhi Chang; Xinyan Lu; Zhongwei Li; Ce Luo; Yanrong Liu; Cheng Yang; et al. (Angiogenesis, 2023)

The clean nitrogen removal process based on solid carbon sources: Research progress and outlook - Heng Wu; Junmei Zheng; Jiawen Wang; Anjie Li; Shuo Sun; Huaiwen Zhang; Yiqing Yao; Guoqiang Zhan (Journal of Cleaner Production, 2023)

The genomic, transcriptomic, and immunological profiles of perineural invasion in pancreatic ductal adenocarcinoma - Shu-Heng Jiang; Rong-Kun Li; De-Jun Liu; Jun-Li Xue; Min-Hao Yu; Shan Zhang; Li-Min Liu; Jun-Feng Zhang; Rong Hua; Yong-Wei Sun; Xu Wang; Qin Yang; et al. (Science China Life Sciences, 2023)

The Nucleus Accumbens CRH–CRHR1 System Mediates Early-Life Stress-Induced Sleep Disturbance and Dendritic Atrophy in the Adult Mouse - Ting Wang; Yu-Nu Ma; Chen-Chen Zhang; Xiao Liu; Ya-Xin Sun; Hong-Li Wang; Han Wang; Yu-Heng Zhong; Yun-Ai Su; Ji-Tao Li; Tian-Mei Si (Neuroscience Bulletin, 2023)

Hemodynamic effects of intravenous bolus injection of iopromide 370 twice in abdominal contrast-enhanced CT and coronary CTA dual-site sequential examinations - Lingru Wang; Haiyan Qiu; Lan Chen; Heng Liu; Junling Liu; Ying Yang; Yueting Sun; Yang Deng; Heng Liu; Xue Li (Medical & Biological Engineering & Computing, 2023)

The first genome sequence of Phomopsis vexans: a fungal pathogen causing Phomopsis blight in eggplant - Zhou Heng; Qian You; Zhiliang Li; Baojuan Sun; Xiaowan Xu; Ying Li; Zhenxing Li; Hengming Wang; Chao Gong; Xiaomei Xu; Tao Li (Biologia, 2022)

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

Episodic Neoproterozoic extension-related magmatism in the Altyn Tagh, NW China: implications for extension and breakup processes of Rodinia supercontinent - Jiang-bo Hao; Chao Wang; Ji-heng Zhang; Liang Liu; Yong-sheng Gai; Hang Li; Zun-pu Yu; Joseph G Meert; Xiao-ping Long; Xiao-kui Sun; Shuai Zhang (International Geology Review, 2022)

Enhanced photosynthetic nitrogen use efficiency and increased nitrogen allocation to photosynthetic machinery under cotton domestication - Zhang-Ying Lei; Heng Wang; Ian J. Wright; Xin-Guang Zhu; Ülo Niinemets; Zi-Liang Li; Dong-Sheng Sun; Ning Dong; Wang-Feng Zhang; Zhong-Li Zhou; Fang Liu; Ya-Li Zhang (Photosynthesis Research, 2021)

Double Weighted Sparse Nonnegative Tensor Factorization for Hyperspectral Unmixing - Heng-Chao Li; Shuang Liu; Xin-Ru Feng; Rui Wang; Yong-Jian Sun (International Journal of Remote Sensing, 2021)

RNA m6A methylation promotes the formation of vasculogenic mimicry in hepatocellular carcinoma via Hippo pathway - Kailiang Qiao; Yantao Liu; Zheng Xu; Haohao Zhang; Heng Zhang; Chao Zhang; Zhi Chang; Xinyan Lu; Zhongwei Li; Ce Luo; Yanrong Liu; Cheng Yang; et al. (Angiogenesis, 2021)

High‐resolution distribution pattern of surface water nitrous oxide along a cruise track from the Okhotsk Sea to the western Arctic Ocean - Liyang Zhan; Jiexia Zhang; Zhangxian Ouyang; Ruibo Lei; Suqing Xu; Di Qi; Zhongyong Gao; Heng Sun; Yuhong Li; Man Wu; Jian Liu; Liqi Chen (Limnology and Oceanography, 2021)
Nitrous oxide in the surface water was measured using an automatic underway system, along with measurements of surface water pCO 2 , dissolved oxygen, salinity, temperature, and sea ice coverage, along a cruise track through the Bering Sea and Chukchi Sea to the Canadian Basin during the 7 th Chinese National Arctic Research Expedition. The results show that, overall, the regions along the cruise track are net sources of N 2 O to the atmosphere. Several N 2 O oversaturation maxima were observed along the cruise track, with an absolute maximum of approximately 60%. According to the hydrographic setting and the distribution patterns of pCO 2 , dissolved oxygen, and sea ice coverage in the study area, it was concluded that the N 2 O oversaturation maxima may result from hydrographic processes, such as mixing of different water masses, upwelling or convection, and possible production beneath the sea ice. Additionally, the lowest value of approximately 90% may result from dilution related to the melting of sea ice. An evaluation of the air–sea flux along the cruise track shows that the continental shelf and upwelling region are N 2 O sources, whereas the study area in the open Arctic Ocean does not show obvious source or sink characteristics.

Single B cells reveal the antibody responses of rhesus macaques immunized with an inactivated enterovirus D68 vaccine - Huiwen Zheng; Zening Yang; Bingxiang Li; Heng Li; Lei Guo; Jie Song; Dongpei Hou; Nan Li; Jinxi Yang; Qiongwen Wu; Ming Sun; Longding Liu (Archives of Virology, 2020)

Detoxification effect of single inoculation and co-inoculation of Oudemansiella radicata and Serratia marcescens on Pb and fluoranthene co-contaminated soil - Lingling Li; Shanshan Guo; Yang Sun; Xuedan Li; Yufeng Gao; Heng Xu; Yunzhen Li (Journal of Soils and Sediments, 2019)

Incidence and clinical correlates of anger attacks in Chinese patients with obsessive-compulsive disorder - Ying-ying Zhang; Heng-fen Gong; Xiao-li Zhang; Wen-juan Liu; Hai-yan Jin; Fang Fang; Sophie Schneider; Elizabeth McIngvale; Chen-cheng Zhang; Wayne K. Goodman; Xi-rong Sun; Eric A. Storch (Journal of Zhejiang University-SCIENCE B, 2019)

Characterization and phylogenetic analysis of the complete mitochondrial genome sequence of Rhyticeros undulatus (Bucerotiformes: Bucerotidae) - Yanyan Chen; Haiya Yan; Jianshu Sun; Chunqing Li; Heng Xiao; Shanyuan Chen (Conservation Genetics Resources, 2019)

24-Epibrassinolide-induced alterations in the root cell walls of Cucumis sativus L. under Ca(NO3)2 stress - Ya-Hong An; Heng Zhou; Ying-Hui Yuan; Lin Li; Jin Sun; Sheng Shu; Shi-Rong Guo (Protoplasma, 2018)

Numerical analysis of effect of baffle configuration on impact force exerted from rock avalanches - YuZhang Bi; YanJun Du; SiMing He; XinPo Sun; DongPo Wang; XinPo Li; Heng Liang; Yong Wu (Landslides, 2018)

Linking a sea level pressure anomaly dipole over North America to the central Pacific El Niño - Ruiqiang Ding; Jianping Li; Yu-heng Tseng; Cheng Sun; Fei Zheng (Climate Dynamics, 2017)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Better knowledge with more gauges? Investigation of the spatiotemporal characteristics of precipitation variations over the Greater Beijing Region - Wen‐Yu Yang; Zhe Li; Ting Sun; Guang‐Heng Ni (International Journal of Climatology, 2016)
Using the hourly precipitation observations from 118 gauge stations and a weather radar in the Greater Beijing Region ( GBR ) during 2008–2012, we investigate the spatiotemporal characteristics of precipitation and discuss the appropriate observational approach for capturing variability of precipitation over this region. In general, the south central and northeastern GBR receives more intense precipitation than other parts. The diurnal cycle of precipitation amount ( PA ) peaks in the evening and decreases till noon, whereas precipitation intensity ( PI ) and precipitation frequency ( PF ) both have two peaks. The stronger peaks of PI and PF occur in the evening whereas the weaker ones appear in the early nighttime and in the afternoon. Remarkable spatial heterogeneity also exists in the diurnal patterns of PA , PI and PF over the GBR . Rainstorms extracted from radar data feature in short duration (11.4 h in average) and highly localized patterns (4.31–20.58/1.85–9.10 km in major/minor radius direction). The estimated diurnal cycles of PA , PI and PF are found to depend on the gauge density in a sensitivity analysis, where a gauge density ratio of 0.6 (corresponding to 30 gauges in total with a representative area of 239.5 km 2 per gauge) is identified as adequate to capture the temporal characteristics of precipitation in the plain area of GBR . However, such a gauge density ratio (i.e. 0.6) is incapable for resolving the spatial characteristics of precipitation in GBR . As such, different instruments (e.g. gauge network, weather radar, etc.) and multiple data sources are suggested to be jointly utilized to better capture the characteristics of rainstorms in GBR .

0.9% saline is neither normal nor physiological - Heng Li; Shi-ren Sun; John Q. Yap; Jiang-hua Chen; Qi Qian (Journal of Zhejiang University-SCIENCE B, 2016)

Complete genome sequence of the first bluetongue virus serotype 7 isolate from China: evidence for entry of African-lineage strains and reassortment between the introduced and native strains - Heng Yang; Minna Lv; Minfei Sun; Liqin Lin; Meilin Kou; Lin Gao; Defang Liao; Heli Xiong; Yuwen He; Huachun Li (Archives of Virology, 2016)

Differences in nitrous oxide distribution patterns between the Bering Sea basin and Indian Sector of the Southern Ocean - Liqi Chen; Jiexia Zhang; Liyang Zhan; Yuhong Li; Heng Sun (Acta Oceanologica Sinica, 2014)

Genetic characterization of avian-origin H3N2 canine influenza viruses isolated from Guangdong during 2006–2012 - Heng Wang; Kun Jia; Wenbao Qi; Minze Zhang; Long Sun; Huanbin Liang; Guohao Du; Likai Tan; Zhenwen Shao; Jiahui Ye; Lingshuang Sun; Zhenpeng Cao; et al. (Virus Genes, 2013)

Purification and characterization of alkaline phosphatase from the gut of sea cucumber Stichopus japonicus - Hai-Tao Wu; Dong-Mei Li; Bei-Wei Zhu; Jing-Heng Cheng; Jin-Jian Sun; Feng-Lin Wang; Yang Yang; Yu-Kun Song; Chen-Xu Yu (Fisheries Science, 2013)

A comparative study of the characteristics of two Coxsackie A virus type 16 strains (genotype B) - ErXia Yang; Heng Zhao; Ying Zhang; JianSheng Liu; Yun Liao; LiChun Wang; PingFang Cui; LiXian Yang; LongDing Liu; ChengHong Dong; ShaoZhong Dong; CongWen Shao; et al. (Science China Life Sciences, 2012)

Aspirin Protects Dopaminergic Neurons Against Lipopolysaccharide-Induced Neurotoxicity in Primary Midbrain Cultures - Fang Wang; Heng Zhai; Luqi Huang; Hui Li; Yan Xu; Xian Qiao; Shenggang Sun; Yan Wu (Journal of Molecular Neuroscience, 2012)

A novel support vector regression model to estimate the phycocyanin concentration in turbid inland waters from hyperspectral reflectance - Deyong Sun; Yunmei Li; Qiao Wang; Chengfeng Le; Heng Lv; Changchun Huang; Shaoqi Gong (Hydrobiologia, 2012)

A neural-network model to retrieve CDOM absorption from in situ measured hyperspectral data in an optically complex lake: Lake Taihu case study - De Yong Sun; Yun Mei Li; Qiao Wang; Heng Lu; Cheng Feng Le; Chang Chun Huang; Shao Qi Gong (International Journal of Remote Sensing, 2011)

The management and planning of citrus orchards at a regional scale with GIS - Wei Wu; Hong-Bin Liu; Heng-Lin Dai; Wei Li; Peng-Shou Sun (Precision Agriculture, 2011)

3D Micro-Crack Propagation Simulation at Enamel/Adhesive Interface Using FE Submodeling and Element Death Techniques - Heng-Liang Liu; Chun-Li Lin; Ming-Tsung Sun; Yen-Hsiang Chang (Annals of Biomedical Engineering, 2010)

Partitioning particulate scattering and absorption into contributions of phytoplankton and non-algal particles in winter in Lake Taihu (China) - Deyong Sun; Yunmei Li; Qiao Wang; Heng Lv; Chengfeng Le; Changchun Huang; Shaoqi Gong (Hydrobiologia, 2010)

Validation of Candidate Reference Genes for the Accurate Normalization of Real-Time Quantitative RT-PCR Data in Rice During Seed Development - Qian-Feng Li; Samuel S. M. Sun; Ding-Yang Yuan; Heng-Xiu Yu; Ming-Hong Gu; Qiao-Quan Liu (Plant Molecular Biology Reporter, 2010)

Inhibitory effects of L- and T-type calcium antagonists on contractions of human detrusor muscle - Jasmin Katrin Badawi; Heng Li; Sigrun Langbein; Sun-Tscheol Kwon; Stefan Kamp; Stephan Bross (European Journal of Clinical Pharmacology, 2006)